PENERAPAN NILAI-NILAI PANCASILA PADA STRATEGI PERANG SEMESTA INDONESIA - Imam Imam Taufik; Lukman Yudho Prakorso; Helda Risman (Strategi Perang Semesta, 2021)
According to the Constitution Act of 1945, the country's defense Indonesia adopts a people's defense, so that his war strategy in the face of threats to use universal war strategy. In the history of the struggle to seize and defend Indonesian independence, all Indonesian people fought together with the army. Where in this struggle, the values of Pancasila have been applied by all Indonesian people. These values are the values of divinity, humanity, unity, mutual cooperation, leadership, and social justice. These values are part of the Pancasila adopted by the Indonesian nation as the basis for the Indonesian state as contained in the preamble to the 1945 Constitution. wisdom of wisdom in deliberation/representation as well as social justice for all Indonesian people. In the struggle to expel the invaders, the heroes have never abandoned divine values as exemplified by Prince Diponegoro, Tuanku Imam Bonjol, Teuku Umar, and others with their jihad spirit. This was also demonstrated by heroes from non-Muslims such as Patimura, Sisingamangaraja XII, and in the war to defend independence there was I Gusti Ngurah Rai with the puputan margarine war in Bali. Not only that, but other Pancasila values are also applied in the universal war waged by the nation's heroes, especially the values of unity, mutual cooperation, leadership, and justice. Therefore, in implementing Indonesia's universal war strategy, the values of Pancasila must always be instilled in all components of the Indonesian nation.